A transdiagnostic evaluation of cortical inhibition in severe mental disorders using Transcranial Magnetic Stimulation. (November 2021) - Mehta, Urvakhsh Meherwan; Ektare, Aboli; Jakhar, Jitender; Basavaraju, Rakshathi; Sanjay, Tarasingh N.; Naik, Shalini S.; Syed, Farooq Ali; Bhargav, Praerna Hemant; Reddy, Preethi V.; Kelkar, Radhika Suneel; Arumugham, Shyam Sundar; Kesavan, Muralidharan; et al.
Abstract: Multiple lines of investigations suggest the presence of cortical inhibition aberrations as central to the phenotypic manifestations of severe mental disorders. Transcranial Magnetic Stimulation (TMS) combined with electromyography can characterize these inhibitory processes in the motor cortex with satisfactory temporal precision. We examined TMS-evoked short- (SICI) and long-interval intracortical inhibition (LICI) and cortical silent period (CSP) as markers of GABAA - (SICI) and GABAB -mediated (LICI and CSP) cortical neurotransmission in symptomatic individuals with mania (n = 40), schizophrenia (n = 76), unipolar depression (n = 86), and OCD (n = 43), and compared them against similar recordings in healthy subjects (n = 125). We hypothesized transdiagnostic GABAA deficits across all the clinical groups and diagnosis-specific GABAB alterations in mania (increased) and OCD (decreased). After controlling for potential confounder variables (gender, education, benzodiazepine prescription, and motor threshold) using the ANCOVA, we observed no significant group difference in SICI (F = 1.04, P  = 0.38), but a significant group effect in LICI (F = 16.29, P  < 0.001) and CSP (F = 3.02, P  = 0.018). Post-hoc analyses revealed that LICI was significantly reduced in OCD but increased in mania and schizophrenia with reference to the healthy group. Similarly, CSP was significantly reduced in OCD and depression groups as compared to the reference group. We observed that LICI and CSP, both followed similar descending gradients from mania through schizophrenia and depression to OCD; with significant elevation in mania, and reduction in depression and OCD, as compared to the healthy group. This pattern of GABAB -mediated cortical inhibition aberrations needs independent validation as potential state-markers of distinct clinical categories. Highlights: We compared TMS-evoked cortical inhibition in mania, depression, OCD, schizophrenia with that in healthy subjects. SICI was not significantly different across the groups, although the clinical groups had small magnitude impairments. LICI was high in mania and schizophrenia and low in depression and OCD. CSP was low in depression and OCD. TMS-derived GABAB -mediated cortical inhibition holds promise as diagnostic biomarkers.